Development and characterization of healthy gummy jellies containing natural fruits - Teixeira-Lemos Edite (De Gruyter, 2021)
The reduction of sugar and the addition of healthier ingredients in gummy jellies brings some improved health characteristics to a product that usually is devoid of nutrition. Therefore, the aim of this study is to develop gummy jellies using natural ingredients, without added sugars or additives, in two varieties: one including orange juice and slightly sweetened with honey (ORH) and the other including puree made from a mixture of berries (BEM). These were submitted to physicochemical, microbiological, and sensorial analyses. Results of microbiological analyses showed that both gummies were suitable for consumption accordingly to EU legislation. The physicochemical analyses allowed making a nutritional evaluation, so that ORH and BEM presented 73.8 kcal/100 g and 39.8 kcal/100 g, respectively, five and nine times lower than similar commercial products. The contribution of macronutrients of ORH and BEM was as follows: 78.0 and 67% from carbohydrates, 21.7 and 33% from proteins, respectively. Regarding the potential functional properties, the antioxidant capacity was 50.4  ±  4.5 mg/L TE for ORH and 83.7  ±  7.6 mg/L for BEM. Sensorial evaluation showed that although the developed gummy jellies were slightly less appreciated than a commercial counterpart, still they were appreciated by members of a panel and particularly the ORH, which was rated with scores almost equal to those of the commercial sample. In addition, the developed gummies showed lower caloric values and higher antioxidant capacity than similar commercial candies. Overall, ORH and BEM gummy jellies could represent an opportunity to provide consumers with a healthier alternative to the common jelly candies available in the market.